A structural property concerning abstract commensurability of subgroups - Grigorchuk, R; Wilson, J (2003)
Further properties of a group Γ introduced by the first author in 1980 (sometimes called the first Grigorchuk group) are established. These are notably that any two infinite finitely generated subgroups of Γ have isomorphic subgroups of finite index and that the generalized word problem for Γ is soluble.